Ocular perfusion in primary angle-closure suspect and primary angle-closure eyes without prior acute angle closure - Reni Philip; Venkateshwaran Kannan; Lingam Vijaya; Rashima Asokan; Shantha Balekudaru; Annadurai Parivadhini; Ronnie George (Oman Journal of Ophthalmology)
BACKGROUND: Acute intraocular pressure (IOP) spike in acute primary angle closure (APAC) decreases ocular blood flow. It is not known if this is true in primary angle-closure (PAC) eyes without prior APAC who may have had subacute attacks. Hence, we aimed to assess the ocular perfusion using optical coherence tomography angiography (OCTA) characteristics in normal, PAC suspect (PACS), and PAC eyes without APAC. MATERIALS AND METHODS: This was a prospective cross-sectional study, which determined patients’ (40–80 years) optic nerve peripapillary perfusion, flux, and macular vessel density (6 mm × 6 mm and 3 mm × 3 mm) in the superficial retinal layer on OCTA. RESULTS: We included 135 eyes of 135 patients (45 per subgroup). The mean age was 59.7 ± 8.3 years. The mean peripapillary perfusion was 44.4% ±1.5% in normal, 44.2% ±1.7% in PACS, and 44.1% ±1.5% in PAC eyes. There was no significant difference between OCTA parameters among normal, PACS, and PAC eyes (P = 0.75 – peripapillary perfusion, 0.92 – flux, 0.58 – 6 × 6 and 0.09 – 3 mm × 3 mm). The maximum recorded IOP was significantly correlated with retinal nerve fiber layer thickness in the PAC group (P = 0.045) but not correlated with the perfusion parameters in any subgroup. The mean deviation on Humphrey visual field was significantly worse in PAC eyes compared to PACS eyes (P = 0.02). CONCLUSION: Similar OCTA parameters were seen in normal, PACS, and PAC eyes without prior APAC, suggestive of absence of vascular factors in eyes without APAC in angle-closure disease. Functional impairment, despite similar structural and perfusion parameters in PAC eyes compared to PACS eyes, may be suggestive of ganglion cell dysfunction prior to loss.